A Novel Vaccine Strategy Employing Serologically Different Chimpanzee Adenoviral Vectors for the Prevention of HIV-1 and HCV Coinfection - Hartnell, Felicity; Brown, Anthony; Capone, Stefania; Kopycinski, Jakub; Bliss, Carly; Makvandi-Nejad, Shokouh; Swadling, Leo; Ghaffari, Emma; Cicconi, Paola; Del Sorbo, Mariarosaria; Sbrocchi, Roberta; Esposito, Ilaria; et al. (Frontiers in Immunology, 2019)
Background: Nearly 3 million people worldwide are coinfected with HIV and HCV. Affordable strategies for prevention are needed. We developed a novel vaccination regimen involving replication-defective and serologically distinct chimpanzee adenovirus (ChAd3, ChAdV63) vector priming followed by modified vaccinia Ankara (MVA) boosts, for simultaneous delivery of HCV non-structural (NSmut) and HIV-1 conserved (HIVconsv) region immunogens. Methods: We conducted a phase I trial in which 32 healthy volunteers were sequentially enrolled and vaccinated via the intramuscular route as follows: 8 received ChAd3-NSmut [2.5x1010 vp] and MVA-NSmut [2x108 pfu] at weeks 0 and 8 and respectively; 8 received ChAdV63.HIVconsv and MVA.HIVconsv at the same interval [5x1010 vp and 2x108 pfu respectively]; 16 were co-primed with ChAd3-NSMut and ChAdV63.HIVconsv followed at week 8 by MVA-NSmut and MVA.HIVconsv [both 1x108 pfu]. Immunogenicity was assessed using peptide pools in ex-vivo ELISpot and intracellular cytokine assays. Vaccine-induced whole blood transcriptome changes were assessed by microarray analysis. Results: All vaccines were well tolerated and no vaccine-related serious adverse events occurred. Co-administration of the prime-boost vaccine regimens induced high magnitude and broad T cell responses that were similar to those observed following immunisation with either regimen alone. Median (interquartile range, IQR) peak responses to NSmut were 3480 (2728-4464) and 3405 (2307-7804) spot-forming cells (SFC)/106 PBMC for single and combined HCV vaccinations respectively (p = 0.8). Median (IQR) peak responses to HIVconsv were 1305 (1095-4967) and 1005 (169-2482) SFC/106 PBMC for single and combined HIV-1 vaccinations respectively (p = 0.5). Responses were maintained above baseline to 34 weeks post-vaccination. Intracellular cytokine analysis indicated that the responding populations comprised polyfunctional CD4+ and CD8+ T cells . Canonical pathway analysis showed that in the single and combined vaccination groups, pathways associated with antiviral and innate immune responses were enriched for upregulated interferon-stimulated genes 24 hours after priming and boosting vaccinations. Conclusions: Serologically distinct adenoviral vectors encoding HCV and HIV-1 immunogens can be safely co-administered without reducing the immunogenicity of either vaccine. This provides a novel strategy for targeting these viruses simultaneously and for other pathogens that affect the same populations. Clinical trial registration: clinicaltrials.gov NCT02362217